Menghapus Istilah Kafir dalam Konteks Berbangsa dan Bernegara di Indonesia; Ikhtiar Kaum Pesantren Mengokohkan Dasar Toleransi Beragama - Moh. Salapudin; Shofa, Insanush (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2020)
One of our classic but always actual problems is intolerance. Religious intolerance itself is caused by many factors, among others; exclusivity understanding and praxis towards religion, sect, or denomination, literal understanding of the verses in each holy book, and injustice in treating other religious communities. The second cause in the author's view does not only stop at a literal understanding of the verses in the holy book, but also on a literal understanding of religious-related themes described in classical Islamic literature such as the term kafir which is classified into four categories, namely kafir. harbi, kafir mu'ahad, kafir musta'man, and kafir dzimmi. The categorization of kafir found in classical Islamic literature has the potential to become the basis for some people to practice intolerant acts in the form of heresy or mention of kafir accompanied by deprivation of the political rights of residents other than Muslims and subverting them. Therefore, a review of the relevance of the term kafir in classical Islamic literature is necessary.